Analytical Study of Some Lightest Nuclei H, He, Li and Be - Hwash, Waleed S.; Saeed, Ahmed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In the present study, the properties of the light elements, namely, H, He, Li, and Be, have been reviewed. Specifically, the nuclear decay of these nuclei has been reviewed. The mystery of the nuclear decay and potential is behind this work. The role of neutron has been investigated. The N/Z ratio has also been investigated in the study to relate the nuclear decay with the ratio. A new formula for nuclear potential has been suggested in the present study. This formula can describe the binding energy potential and the decayed particle energy depending on the N/Z ratio.